The influence of social and symbolic cues on observers' gaze behaviour. - Hermens, Frouke; Walker, Robin (British Journal of Psychology, 2016)
Research has shown that social and symbolic cues presented in isolation and at fixation have strong effects on observers, but it is unclear how cues compare when they are presented away from fixation and embedded in natural scenes. We here compare the effects of two types of social cue (gaze and pointing gestures) and one type of symbolic cue (arrow signs) on eye movements of observers under two viewing conditions (free viewing vs. a memory task). The results suggest that social cues are looked at more quickly, for longer and more frequently than the symbolic arrow cues. An analysis of saccades initiated from the cue suggests that the pointing cue leads to stronger cueing than the gaze and the arrow cue. While the task had only a weak influence on gaze orienting to the cues, stronger cue following was found for free viewing compared to the memory task.